TAS2R38 polymorphisms and oral diseases in Thais: a cross-sectional study - Sawita Khimsuksri; Jarin Paphangkorakit; Waranuch Pitiphat; Susan Elaine Coldwell (BMC, 2022)
Abstract Background Polymorphisms at positions 49, 262, and 296 in the TAS2R38 bitter taste receptor gene result in two common genetic haplotypes, PAV and AVI, named for the resulting amino acid substitutions. TAS2R38 genotype has been previously associated with caries risk in children. This study aimed to identify TAS2R38 polymorphisms among Thais and to explore any association between genotype and oral diseases. Methods Patients seeking care at Khon Kaen University Dental Hospital in Thailand were recruited to participate in the study. Saliva was collected for DNA extraction and genotyping. Patients completed a questionnaire to collect demographic variables and assess oral self-care behaviors. A calibrated dentist conducted an examination that included periodontal charting and recording of decayed, missing, and filled teeth (DMFT). Results A total of 250 patients (19-75 years) were enrolled in the study (116 males). Two haplotypes, PAV (67.2%) and AVI (32.8%) were found, resulting in 3 diplotypes; PAV/PAV (46.0%), PAV/AVI (42.4%) and AVI/AVI (11.6%). DMFT and periodontal status of 238 participants were recorded. The three diplotype groups were similar in age, sex, socio-economic indicators, oral self-care, and number of teeth. The odds of having periodontal disease, defined as at least one site with probing depth ≥ 5 mm, were lower in AVI/AVI and PAV/AVI compared with PAV/PAV. PAV/AVI tended to have less DMFT, while AVI/AVI tended to have more DMFT compared with PAV/PAV, however these trends did not reach statistical significance. Conclusions The frequency distribution of TAS2R38 genotypes was similar to that reported for other Asian populations. AVI/AVI genotype was associated with decreased prevalence of periodontal disease among Thai dental patients, whereas there was no significant association between TAS2R38 genotype and prevalence of tooth decay in this patient population.